‘Tunisian Question’ in Franco-Italian Relations (1922—1928) - T. P. Nesterova (Научный диалог)
The article is devoted to the development of relations between France and Italy in the context of the status of the Italian population of Tunisia issue. Thanks to the agreements reached by the Italian states and the government of Tunisia, in the first half of the 19th century mass emigration of Italians began to Tunisia, as a result, by the end of the 19th century, a significant Italian diaspora had formed in Tunisia. The establishment of a French protectorate over Tunisia led to the question of the status of the Italian population of Tunisia, which was eventually settled by the Franco-Italian convention of 1896. After the First World War, France refused to comply with the decisions of 1896. The French government set itself the goal of naturalizing Italians in Tunisia. The Italian government strongly opposed such a policy. The negotiations did not lead to a settlement of the conflict. The place of the ‘Tunisian question’ in relations between Italy and France in the 1920s is analyzed, the numerous discussions of the problem of the status of Italians in Tunisia and Italy’s attempts at least to maintain the situation, that existed in accordance with the 1896 convention, are considered in the article. It is proved that Tunisia, with its large Italian diaspora, occupied a significant place in the African policy of Italy during the period of fascism. It is substantiated that the period of the 1920s was essentially the preparatory work for a more serious discussion of the colonial problems that arose between France and Italy, which resulted in the Laval-Mussolini agreement of 1935.